PENGARUH TERAPI AL-QUR’AN SURAT AL-BAQARAH : 9 TERHADAP NILAI KARAKTER KEJUJURAN MELALUI BIMBINGAN KELOMPOK DI SMP KARTIKA 1-5 PEKANBARU - Rusliyana Rusliyana; Tri Umari; Siska Mardes (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of Al-Qur'an Al-Baqarah therapy: 9 through group guidance on honesty character values of Kartika 1-5 Pekanbaru Middle School students. The research method used is a quantitative method with the type of pre-experimental one group pretest-posttest research. The subjects of this study were seventh grade students of Kartika 1-5 Pekanbaru Middle School with a low honesty character value of 8 people. The instrument of data collection used is a questionnaire using a modified Likert scale. The data analysis technique used is the Non Parametric statistical technique using the Wilcoxon Test and the Spearman Ranking Test. The results showed that the honesty character values of students before being given Al-Qur'an therapy Surat Al-Baqarah: 9 through group guidance were in the low category of 75% and in the medium category of 25%, after being given Al-Al Qur'an Al-Baqarah Therapy : 9 through group guidance the value of students' honesty character has increased in the high category by 75% and in the medium category by 25%. Based on the Wilcoxon Test there were significant differences in the honesty value of students' characters before and after Al-Baqarah: 9 therapy was given through group guidance with a significance value of 0.012 <α 0.05. Based on the Spearman Ranking Test, it can be concluded that the relationship between Qur'anic Al-Baqarah therapy: 9 through group guidance with student honesty character values is in the high category of 0.898 or 80.6%. Next to find out the detemination coefficient as follows: (rs) 2 = (0.898) 2 = 0.806. This means that the effects of Al-Qur'an Al-Baqarah therapy: 9 through group guidance services to improve students' honesty character values are 80% while 20% are influenced by other factors that come from within students and from environmental students.Key Words: Al-Qur'an Therapy Surat Al-Baqarah: 9, Honesty Character Value,Group Guidance.